Dear Zoo - Campbell, Rod (London Campbell Books, 2007)
A fresh, new look for a classic children's book!
Include Colour Illustrations
Keywords: Zoo animals -- Pictorial works -- Juvenile fiction -- Pets -- Pictorial works -- Juvenile fiction